Growth Regimes in a Structural Economic Dynamic Approach to the Neo-Kaleckian Model - Araujo, Ricardo Azevedo; Teixeira, Joanílio (Brazilian Keynesian Review, 2016)
Following the insight that profits influence investment, providing not only the motive for it but also the means,we consider the natural rate of profit as one of the determinants of investment in a disaggregated version of the Neo-Kaleckian model of economic growth.By adopting this approach, it is shown that the structural economic dynamic is conditioned not only to the patterns of evolving demand and diffusion of technological progress but also to the distributive features of the economy, which can give rise to particular regimes of economic growth. From this perspective, it is possible to conclude that a wage-led regime is the most probable outcome in a closed economy where the natural rate of profit is one of determinants of investment. Following the insight that profits influence investment, providing not only the motive for it but also the means,we consider the natural rate of profit as one of the determinants of investment in a disaggregated version of the Neo-Kaleckian model of economic growth.By adopting this approach, it is shown that the structural economic dynamic is conditioned not only to the patterns of evolving demand and diffusion of technological progress but also to the distributive features of the economy, which can give rise to particular regimes of economic growth. From this perspective, it is possible to conclude that a wage-led regime is the most probable outcome in a closed economy where the natural rate of profit is one of determinants of investment.